The Effectiveness of Reality Group Counseling with Confrontation Techniques to Reduce Smartphone Addiction Symptoms in College Students - Ulfatari, Nursiah; Eddy Wibowo, Mungin; Japar, Muhammad (Jurnal Bimbingan Konseling, 2022)
Smartphone addiction is a problem experienced by students in academic and social environments. The reality group counseling with confrontation technique is predicted to be able to reduce student’s smartphone addiction. This study aimed to test the effectiveness of group counseling using a confrontation approach to reduce the level of smartphone addiction in college students. It study used an experimental pretest-posttest control group design. The subjects were 14 college students who were divided into two groups. Research subjects were selected using a purposive sampling technique with the criteria of college students who had a high level of smartphone addiction. The data were taken using the Smartphone Addiction Inventory (SPAI) instrument which was adapted into Indonesian with a reliability level of .90 (alpha chronbach). Those were analyzed quantitatively using the Wilcoxon sign-rank test. The results of data analysis showed that group counseling using a reality counseling approach with confrontation technique could effectively reduce the level of smartphone addiction in students. The implications of the research results are presented in the discussion.